Structural and thermodynamic studies of the tobacco calmodulin-like rgs-CaM protein - Makiyama, Rodrigo K. [UNESP]; Fernandes, Carlos A.H. [UNESP]; Dreyer, Thiago R. [UNESP]; Moda, Bruno S. [UNESP]; Matioli, Fabio F. [UNESP]; Fontes, Marcos R.M. [UNESP]; Maia, Ivan G. [UNESP] (Elsevier, 2016)
The tobacco calmodulin-like protein rgs-CaM is involved in host defense against virus and is reported to possess an associated RNA silencing suppressor activity. Rgs-CaM is also believed to act as an antiviral factor by interacting and targeting viral silencing suppressors for autophagic degradation. Despite these functional data, calcium interplay in the modulation of rgs-CaM is still poorly understood. Here we show that rgs-CaM displays a prevalent alpha-helical conformation and possesses three functional Ca2+-binding sites. Using computational modeling and molecular dynamics simulation, we demonstrate that Ca2+ binding to rgs-CaM triggers expansion of its tertiary structure with reorientation of alpha-helices within the EF-hands. This conformational change leads to the exposure of a large negatively charged region that may be implicated in the electrostatic interactions between rgs-CaM and viral suppressors. Moreover, the kd values obtained for Ca2+ binding to the three functional sites are not within the affinity range of a typical Ca2+ sensor.
Keywords: Ca2+-binding protein; Calmodulin-like protein; rgs-CaM